Creative Energy Enterprise / Zailiya Mohamad Yatim... [et al. - Mohamad Yatim, Zailiya; Idin, Suraya; Selamat, Saliyana; Nasir, Noor Azizah; Abu Bakar, Rima Melati (2000)
Creative Energy Enterprise is a partnership company that started on 1 January 2001. Their main business is making plans and models for constructions. They were based in Alor Setar ,Kedah